Response surface methodology (RSM) analysis of antipyretic extracted from Aquilaria Subintegra leaves: article / Aiman Shazni Sa’imin, Habsah Alwi - Sa’imin, Aiman Shazni; Alwi, Habsah
In this study, the optimization condition for extraction of antipyretic properties known as acetaminophen inside the Aquilaria Subintegra leaves was analyze using response surface methodology (RSM). The objective of this study was to determine the optimum condition for extraction of Aquilaria Subintegra leaves by using RSM and to investigate the effect of drying temperature on extraction of Aquilaria Subintegra leaves. RSM use a series of data to obtain an optimal response with minimal effort. Effect of drying temperature on the for the concentration of extraction on Aquilaria Subintegra leaves was studied and the data obtained will be inserted to second-order polynomial equation using multiple regression analysis and analyzed by analysis of variance (ANOVA) to determine the importance of the model. The extraction of the compound on different drying temperature and type of leaves was based on the previous study. Based on the result, the model F-value of 2.75 and Prob>F of 0.1102 indicate that the model is suitable to use. The high value of R2 which is 0.6623 and smaller value of adjusted R2 which is 0.4211 was compared to show the model was sufficient. The predicted optimum of drying temperature was 30ºC. The predicted value of concentration of the compound on Aquilaria leaves was 2.697 μg/mL and the error calculated was based on the previous study by taking the average value of error on both of the studies which is 2.04%. There is no actual value in this study since there are no validation experiment was run to prove the optimum value. In conclusion, the end results show that the response surface methodology is succeeded in determining the optimum drying temperature of Aquilaria Subintegra.